Sacred Vā-Rhythms: A Book Review of Winston Halapua's Waves of God's Embrace, Sacred Perspectives from the Ocean (2008) - Fa'avae, David Taufui Mikato (Art/Research International, 2024)
This book review is a talanoa (discussion) with Winston Halapua’s 2008 text, Waves of God’s Embrace: Sacred Perspectives from the Ocean. This review is an interpretation and evaluation of the text and Halapua’s narrative musings. Readers are invited to engage with Indigenous concepts and forms of creative criticality, fronting Oceania meaning-making and sense-making through storytelling, poetry, and proverbial or wise sayings. In my review, I employ sacred vā-rhythms to engage in talanoa with key themes, ideas, and insights noted by Halapua, a well-respected religious leader and academic. I offer questions and provocations about God’s embrace and the ways in which sacred vā is framed today as being in-relationship with the more-than-human world (i.e., the fonua-vanua-whenua and moana) for Tongan as well as Oceania families across Oceania and the diaspora.